Effect of baffles on performance of fluid catalytic cracking riser - Shah, Milin; Pareek, Vishnu; Evans, G.; Utikar, Ranjeet (2017)
Increasing demand of automobile fuel and a need to process heavier crude oil makes it imperative to find improvements to the design of existing fluid catalytic cracking (FCC) units. Several modifications to the design of the riser section of FCC units have been suggested in previous studies including: improved feed nozzle designs, multiple nozzle configurations, internal baffles, and novel two-stage-riser systems. In this study, we investigate the effects of baffles on the performance of FCC risers using computational fluid dynamics simulations. In this study, predictions from a basis model (without baffles) are compared with those from four different configurations including: (i) 5-cm baffles at 5-m spacing, (ii) 7.5-cm baffles at 5-m spacing, (iii) 10-cm baffles with 5-m spacing, (iv) 10-cm baffles at 2.5-m spacing, and (v) 10-cm baffles at 1-m spacing. The baffles force the catalyst away from walls toward the center of the riser, enhancing the radial dispersion of the catalyst and the heat transfer inside the riser. The use of longer baffles and smaller spacings further increases the dispersion, yielding more homogeneous radial profiles. The changes in the radial dispersion result in variations in the conversion, yields, and pressure drops. The baffles increase conversion of vacuum gas oil (VGO) and the yield of gasoline. However, the simulations showed that longer baffles and a larger number of baffles did not always give a higher yield or higher conversion. Among the simulated configurations, the 5-cm baffles at 5-m spacing gave the highest conversion of VGO, whereas the 10-cm baffles at 1-m spacing resulted in the highest yield of the gasoline. Thus, rational optimization of baffle configurations is required to achieve optimal performance.